INSTILLING TOLERANCE VALUES IN CULTURAL PLURALISM EARLY CHILDHOOD EDUCATION - Hafni, Nurlaili Dina; Prasetyo, Agus Fathoni; Mubaidilla, Irfa'i Alfian; Najmina, Nahwatun (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2024)
Indonesia is a country rich in ethnic, religious, cultural, customs, language and background diversity, which often causes shifts and conflicts in society. Awareness and recognition of this diversity is known as pluralism, which includes cultural, political and religious aspects. Instilling the values ​​of pluralism and tolerance is closely related to Indonesian society's awareness of existing differences. One of the ways that is considered the most effective for instilling the values ​​of tolerance and pluralism between religious communities is through education. In early childhood, their potential includes aspects of religious-moral, physical-motor, social-emotional, language and artistic values, so that their development period must be directed at instilling moral-religious, cognitive, social-emotional, physical values. -balanced motor skills, language and art as the basis for the formation of a complete person. To implement this good behavior, an effective educational approach is needed from parents and teachers, because the school and family environment greatly influences a child's personality. Therefore, it is important to instill good attitudes in children's lives from an early age so that these values ​​can be ingrained well into adulthood. Based on this background, this research was carried out with the title "Instilling the Value of Tolerance in Cultural Pluralism in Early Childhood."